Clash of career and family: fertility decisions after job displacement - Emilia Del Bono; Andrea Weber; Rudolf Winter-Ebmer (University of Essex, Institute for Social and Economic Research (ISER), 2007)
In this paper we investigate how fertility decisions respond to unexpected career interruptions which occur as a consequence of job displacement. Using an event study approach we compare the birth rates of displaced women with those of women unaffected by job loss after establishing the predisplacement comparability of these groups. Our results reveal that job displacement reduces average fertility by 5 to 10% in both the short and medium term (3 and 6 years) and that these effects are largely explained by the response of white collar women. Using an instrumental variable approach we provide evidence that the reduction in fertility is not due to the income loss generated by unemployment but arises because displaced workers undergo a career interruption. These results are interpreted in the light of a model in which the rate of human capital accumulation slows down after the birth of a child and all specific human capital is destroyed upon job loss.
Keywords: 330